A Comparison of Students’ Preferences in Online Algebra Instruction Pre- and Post-Covid-19 - Akcay Ozkan, Zeynep; Budak, Sirin (International Journal of Interactive Mobile Technologies (iJIM), 2021)
This study is aimed towards understanding students’ preferences in online learning of College Algebra at a community college in the United States, before and after the Covid-19 pandemic. We analyze the results of Student Satisfaction surveys administered during Fall 19, Spring 20 and Fall 20 semesters. The classes were partially or fully online with synchronous and asynchronous components such as face-to-face and/or virtual meetings, pre-recorded video lessons, assignments through online homework platforms, and discussion board assignments. Our analysis show that students found face-to-face meetings most helpful, when classes were taught partially online. After the transition to online teaching, virtual meetings did not directly replace the face-to-face meetings, instead online homework platforms were preferred. We find that students ultimately started utilizing all components of online classes on an equal basis. Our results reflect students’ adjustment to online teaching, taking more advantage from asynchronous course components and becoming active learners over time.